The Use of Elicitation Technique in Teaching Speaking Skills at Grade Eight Junior High School - Renni Vorkia Sinaga; Isli Iriani Indiah Br. Pane (Universitas Negeri Medan, 2023)
This study aims to identify and classify of the use of elicitation and to discover the reasons of using elicitation technique in teaching speaking skills at grade eighth junior high school. A qualitative case study used in this study. The subject of the study was one English teacher at SMP Swasta Methodist 9 Medan. The data were collected for three meeting by using observation, recording and interview. The data analyzed by Doff (1988) theory of elicitation. The finding of this study shows that there were three types elicitation technique namely, asking question 22 (55%), asking question combined with picture about 5 (12,5%), asking question combined with text and dialogues about 13 (32,5%). It means that asking question placed the highest frequency of use to encourage students to talk. Also, there were reasons of using elicitation that had gotten from teachers interview namely to encourage students to participate in the classroom, to know students understanding, to build students interesting to the material, to motivate the students to participate by stimulating their curiosity, to activate students’ thinking or students’ imagination. It can be concluded that there is a positive impact in class interaction using eliciting techniques. This research will assist teachers in interacting with students in the teaching and learning process to stimulate students' speaking in class interactions.Keywords: Speaking skills, Teaching Speaking, Elicitation, Doff Theory , Recount Text